Manfaat Pemberian Stik Gembili Untuk Menambah Berat Badan Anak - Maya Septriana; Myrna Adiyanti; Rini Hamsidi; Dwi Indah; Galuh Puja; Onny Priskila (Jurnal Kesehatan, 2022)
50-60%  parents reported that their child had feeding problems. One of the specific nutritional interventions by giving functional foods such as Gembili (Dioscorea esculenta L.). Gembili stick intervention in toddlers was using experimental quantitative research design and data collection methods with "pre-posttest group design" on stunting toddlers. Subjects did a pretest with anamnesis and anthropometric examination. Subjects were given the gembili stick formula 3 times a day for 14 days, the amount was to 100 grams. After 14 days, the evaluation data were analyzed using the T test to determine the effect of consuming gembili sticks in increasing the weight of stunting toddlers. The result of gembili sticks which has a yellowish-brown color, tastes delicious, and crunchy. The sticks are packaged in plastic packaging, measured according to the caloric needs of each subject. The results of the gembili stick intervention on body weight have a sig value. (2 tailed) 0.028 < (0.05), which means that there is a difference in body weight before and after giving gembili sticks. The results of the intervention body mass index have a sig. (2 tailed) 0.027 < (0.05), which means that there is a difference in body mass index before and after giving gembili sticks. Consumption of gembili sticks for 14 days can significantly increase body weight and body mass index in children.